FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU DI MADRASAH ALIYAH DARUL HIKMAH PEKANBARU - Meriza Indah Pratiwi; Suarman Suarman; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRAKIn the world of teacher education are at the forefront . This means that without the participation of the teacher education quality would be impossible to run properly . For that teachers are required to have a high performance , because to the high performance of teachers can carry out their duties optimally . The level of teacher performance is certainly not out of the two factors, both factors originating from within oneself ( internal factors ) and factors that originate from outside or the environment ( external factors ) that will bring changes to the teachers' performance in school . This research was conducted in Madrasah Aliyah Darul Hikmah Pekanbaru . The population of this study amounted to 46 people . The sample in this study was 42 . Data collection techniques by using a questionnaire distributed directly to teachers at Madrasah Aliyah Darul Hikmah. Then the results of the data from the questionnaire was examined by the Head Master to be proved correct. The analysis used is multiple linear regression analysis . Data processing were performed with SPSS version 16.0 forWindows. The results showed that Factor Internal and External factors affect teacher performance in Madrasah Aliyah Darul Hikmah Pekanbaru . With internal factors tcount 5.272 > 2.023 ttable and external factors tcount 2,740 > 2,023 ttable . As for the value of Fcount 50.110 > 3.238 Ftable so it is concluded that internal factors and external factors significantly influence the performance of teachers . The coefficient of determination ( R2 ) obtained 0,720 or 72.0 percent . This means that the variable factors internal and external factors contributing variables in explaining teacher performance variables by 72.0 percen. The remaining 28.0 percent is influenced by other variables not examined in this study . Suggestions for this research that in carrying out his duties at the school , the teacher must be able to be professional not to family problem , work environment, etc. mixed with work in schools because it may interfere with the performance of teachers in the school.Keywords : Internal Factors , External Factors , Teacher Performance